2014
DOI: 10.1109/tpds.2013.267
|View full text |Cite
|
Sign up to set email alerts
|

Can P2P Technology Benefit Eyeball ISPs? A Cooperative Profit Distribution Answer

Abstract: Peer-to-Peer (P2P) technology has been promoting the development of Internet applications, like Video on Demand (VoD) and file sharing. However, under the traditional pricing mechanism, the fact that most P2P traffic flows among peers can dramatically decrease the profit of ISPs, who may take actions against P2P and impede the adoption of P2P-assisted applications. So far, there is no proper profit distribution mechanism to solve this problem. In this paper, we develop a mathematical framework to analyze such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…By observing problem (4), we note that the problem is an integer-programming problem [9]. As the parameters c m and c n,k to be optimized are in terms of integers, there exists no polynomial time-complexity algorithm to solve the problem [19].…”
Section: Nbs Based Vr Allocationmentioning
confidence: 99%
See 2 more Smart Citations
“…By observing problem (4), we note that the problem is an integer-programming problem [9]. As the parameters c m and c n,k to be optimized are in terms of integers, there exists no polynomial time-complexity algorithm to solve the problem [19].…”
Section: Nbs Based Vr Allocationmentioning
confidence: 99%
“…Hence, the performance variation of the MNO or a WSP (due to e.g., the variation of channel conditions) would not lead to the performance degradation of other WSPs (or the MNO). We use the Nash bargaining cooperative game [9,10] to model the VR allocation problem. The formulated game is termed as the cooperative VR allocation game (VRAG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hande et al [16] set up a two-sided model in a rate allocation market and concluded that subsidizing end users' cost of connectivity by pricing content providers may benefit both end users and CPs. Xu et al [18] proposed a cooperative profit-distribution model for eyeball ISPs and peer-assisted content providers based on Nash Bargaining Solution. Authors in [13,14] studied the profit-sharing mechanism of multi-lateral ISP settlements.…”
Section: Related Workmentioning
confidence: 99%
“…The other key work of EC is to guarantee the fairness of profit distribution inside, which is the distribution of the entire profit gained by EC to each individual prosumer inside EC. It can affect the participation willingness of prosumers (Xu et al, 2014). A Nash-type non-cooperative game theory approach distributes prosumers' profit by introducing a spontaneous competition among them (Long et al, 2019;Jing et al, 2020).…”
Section: Introductionmentioning
confidence: 99%